Heritability of dietary fiber content and grain yield in common bean populations - Londero, Patrícia Medianeira Grigoletto; Ribeiro, Nerinéia Dalfollo; Filho, Alberto Cargnelutti; Rodrigues, Josana de Abreu; Antunes, Irajá Ferreira (Pesquisa Agropecuaria Brasileira, 2006)
The objective of this study was to estimate the heritability and gain from selection of dietary fiber content (soluble, insoluble and total) and grain yield, in populations obtained from five different crossings, and to identify more adequate population considering different fraction fibers. Crossings were performed in greenhouse among the genitors CNFP 8100, FT 96-1282, Varre-Sai and Valente. The populations obtained (parents, F1 and F2) were assessed in the field during spring/summer of 2003/2004, using a randomized complete blocks experimental design. Significant differences were obtained for total dietary fiber, however no genetic variability was observed for soluble and insoluble dietary fiber and grain yield in populations. Positive phenotypic correlation between insoluble and total dietary fiber was observed. F2 selection plants in segregant population, developed from Valente x Varre-Sai, can be effective in the development of bean germplasm with higher total dietary fiber, because of the high broad-sense heritability estimates and highest gain from selection obtained in the combination.
Keywords: Phaseolus vulgaris; genetic variance; gain from selection; correlation